Sleep-related changes in cardiovascular autonomic regulation in left coronary artery ligation rats: Neural mechanism facilitating arrhythmia after myocardial infarction. (15th December 2016) - Lin, Wei-Lun; Lo, Li-Wei; Chen, Hau-Ruey; Lai, Chun-Ting; Yamada, Shinya; Liu, Shin-Huei; Chou, Yu-Hui; Chen, Shih-Ann; Fu, Yun-Ching; Kuo, Terry B.J.
Abstract: Background: Autonomic imbalance with increased sympathetic and decreased parasympathetic activities is observed in patients after myocardial infarction (MI). We aimed to investigate sleep-related changed in autonomic regulation in left coronary artery (LCA) ligation rats. Methods: Wireless transmission of polysomnographic recording was performed in sham and LCA ligation male rats during normal daytime sleep with and without atenolol treatment. Spectral analyses of the electroencephalogram (EEG) and electromyogram (EMG) were evaluated to define active waking (AW), quiet and paradoxical sleeps (QS, PS). Cardiac autonomic activities were measured by analyzing the power spectrum of heart rate variability (HRV). EEG, EMG and HRV were recorded over 6 h for consecutive 3 days in all groups. Results: In LCA ligation group, there were higher LF and LF/HF ratio on QS phase, but not AW and PS phases, compared to atenolol treated sham and LCA ligation groups, respectively. The HF component was not significantly changed on all groups in both sleep and awake phases. Sleep interruption was more frequent in LCA ligation rats compared to sham, and it was not found in LCA ligation with atenolol treatment group. Increased AW, PS and decreased QS time were noted in LCA ligation group, compared to sham and it was restored to baseline in LCA ligation with atenolol treatment group. Conclusions: Our results demonstrate significant sleep fragmentations with sympathetic hyperactivity during QS stages after MI, and atenolol could restore the autonomic dysfunction and sleep disturbance. The finding explains the cause of sleep-related fetal arrhythmia and sudden cardiac death after MI.